Constraining baryonic feedback and cosmology with weak-lensing, X-ray, and kinematic Sunyaev–Zeldovich observations. Issue 3 (7th June 2022) - Schneider, Aurel; Giri, Sambit K; Amodeo, Stefania; Refregier, Alexandre
ABSTRACT: Modern weak-lensing observations are becoming increasingly sensitive to baryonic feedback processes which are still poorly understood. So far, this challenge has been faced either by imposing scale-cuts in the data or by modelling baryonic effects with simple, one-parameter models. In this paper, we rely on a more general, seven-parameter prescription of baryonic feedback effects, which is primarily motivated by observations and has been shown to agree with a plethora of hydrodynamical simulations. By combining weak-lensing data from the Kilo-Degree Survey (KiDS-1000) with observations of gas around galaxy clusters, we are able to constrain baryonic parameters and learn more about feedback and cosmology. In particular, we use cluster gas fractions from X-ray data and gas profiles from kinematic Sunyaev–Zeldovich (kSZ) observations to provide evidence for baryonic feedback that is stronger than predicted by most hydrodynamical simulations. In terms of the matter power spectrum, we report a beyond-per cent effect at wave-modes above k ∼ 0.1–0.45 h Mpc^-1 and a maximum suppression of 12–33 per cent at k ∼ 7 h Mpc^-1 (68 per cent confidence level). Regarding the combined parameter Σ8 = σ8 (Ωm /0.3) 0.58, we find the known tension with the Planck satellite data to be reduced from 3.8σ to 2.9σ once baryonic effects are fully included in the analysis pipeline. The tension is further decreased to 2.6σ when the weak-lensing data are combined with X-ray and kSZ observations. We conclude that, while baryonic feedback effects become more important in modern weak-lensing surveys, they are unlikely to act as the main culprit for the observed Σ8 -tension.